DIGITAL SCREEN EXPOSURE AND DRY EYE DISEASE: A REVIEW OF CLINICAL AND PATHOPHYSIOLOGICAL PERSPECTIVES - Stadnik, Aleksandra; Stankowski, Wiktor; Jurkowska, Klaudia; Stanik, Martyna; Mahoney, Eleonora Y.; Bełc, Ewa; Reliszka, Agata; Trzyna, Elżbieta; Gliwa, Anna; Górak, Joanna (International Journal of Innovative Technologies in Social Science, 2026)
Background: Dry eye disease (DED) is one of the most common ocular surface diseases and is associated with disruption of tear film homeostasis, tear instability, and chronic inflammation. With the increasing use of digital devices in everyday life, their potential impact on the development and severity of DED symptoms is increasingly being analyzed. Aim: The aim of this narrative review was to present current data on the relationship between digital device use and dry eye disease, with particular emphasis on pathophysiological mechanisms, epidemiological data, and possible prevention and treatment options. Methods: A literature review was conducted using publications available in the PubMed, Scopus, and Google Scholar databases. Clinical and epidemiological studies, as well as review articles on ocular surface disorders associated with digital exposure, were included. Results: The analyzed data indicate that prolonged screen use may contribute to tear film destabilization through decreased blinking frequency, increased tear evaporation, and meibomian gland dysfunction. Numerous studies have also observed a higher incidence of DED symptoms in individuals who use digital devices extensively. Conclusion: Growing exposure to screens is making screen-related dry eye an increasingly common clinical problem in modern ophthalmology. Being a modifiable factor, it creates the opportunity to implement interventions that reduce the severity of DED symptoms and improve patient comfort.